Single-Cell Proteomics Reveals the Defined Heterogeneity of Resident Macrophages in White Adipose Tissue - Félix, Inês; Jokela, Heli; Karhula, Joonas; Kotaja, Noora; Savontaus, Eriika; Salmi, Marko; Rantakari, Pia (Frontiers in Immunology, 2021)
Adipose tissue macrophages (ATMs) regulate homeostasis and contribute to the metabolically harmful chronic inflammation in obese individuals. While evident heterogeneity of resident ATMs has been described previously, their phenotype, developmental origin, and functionality remain inconsistent. We analyzed white adipose tissue (WAT) during homeostasis and diet interventions using comprehensive and unbiased single-cell mass cytometry and genetic lineage tracking models. We now provide a uniform definition of individual subsets of resident ATMs. We show that in lean mice, WAT co-harbors eight kinetically evolving CD206+ macrophage subpopulations (defined by TIM4, CD163, and MHC II) and two CD206– macrophage subpopulations. TIM4–CD163+, TIM4–CD163– and CD206– macrophage populations are largely bone marrow-derived, while the proliferating TIM4+CD163+ subpopulation is of embryonic origin. All macrophage subtypes are active in phagocytosis, endocytosis, and antigen processing in vitro, whereas TIM4+CD163+ cells are superior in scavenging in vivo. A high-fat diet induces massive infiltration of CD206– macrophages and selective down-regulation of MHC II on TIM4+ macrophages. These changes are reversed by dietary intervention. Thus, the developmental origin and environment jointly regulate the functional malleability of resident ATMs.